Development of high-temperature permanent magnet synchronous motor for autonomous robotic navigation: a design and finite element analysis approach - M, Anand; M, Sundaram; P, Sivakumar; A, Angamuthu (Bulletin of the Polish Academy of Sciences Technical Sciences, 2024)
Traditional industrial robots come with prime movers, i.e. electric motors (EMs), which range from a few hundred to just a few kilo watts of power ratings. However, for autonomous robotic navigation systems, we require motors which are lightweight with the aspect of high torque and power density. This aspect is very critical when the EMs in robotic navigations are subjected to harsh high temperature survival conditions, where the sustainability of the performance metrics of the electromagnetic system of the EMs degrades with the prevailing high temperature conditions. Hence, this research work addresses and formulates the design methodology to develop a 630 W high temperature PMSM (HTPMSM) in the aspect of high torque and power density, which can be used for the autonomous robotic navigation systems under high temperature survival conditions of 200°C. Two types of rotor configurations i.e. the surface permanent magnet type (SPM) and the interior permanent magnet type (IPM) of HTPMSM are examined for its optimal electromagnetic metrics under the temperature conditions of 200◦C. The 630 W HTPMSM is designed to deliver the rated torque of 2 Nm within the volumetric & diametric constraints of DxL, which comes at 80 × 70 mm at the rated speed of 3 000 rpm with the survival temperature of 200°C and target efficiency greater than 90%. The FEM based results are validated through the hardware prototypes for both SPM and IPM types, and the results confirm the effectiveness of the proposed design methodology of HTPMSM for sustainable autonomous robotic navigation applications.